2012
DOI: 10.4097/kjae.2012.62.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive bradycardic events during shoulder arthroscopic surgery under interscalene brachial plexus blocks

Abstract: Sudden, profound hypotensive and bradycardic events (HBEs) have been reported in more than 20% of patients undergoing shoulder arthroscopy in the sitting position. Although HBEs may be associated with the adverse effects of interscalene brachial plexus block (ISBPB) in the sitting position, the underlying mechanisms responsible for HBEs during the course of shoulder surgery are not well understood. The basic mechanisms of HBEs may be associated with the underlying mechanisms responsible for vasovagal syncope, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 63 publications
(85 reference statements)
2
24
0
3
Order By: Relevance
“…Therefore, ISBPB appears to cause failure of the sympathovagal balance to shift toward sympathetic predominance after the patients transitions to the sitting position. Horner's syndrome, resulting from ipsilateral stellate ganglion blockade due to extended distribution of local anesthetics from the interscalene groove to the ipsilateral stellate ganglion, is thought to contribute to HBEs [2,25]. A recent abstract attributed the shift in the sympathovagal balance toward parasympathetic tone (decreased LF/HF) both in the supine and sitting position after ISBPB to ipsilateral stellate ganglion blockade [8].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ISBPB appears to cause failure of the sympathovagal balance to shift toward sympathetic predominance after the patients transitions to the sitting position. Horner's syndrome, resulting from ipsilateral stellate ganglion blockade due to extended distribution of local anesthetics from the interscalene groove to the ipsilateral stellate ganglion, is thought to contribute to HBEs [2,25]. A recent abstract attributed the shift in the sympathovagal balance toward parasympathetic tone (decreased LF/HF) both in the supine and sitting position after ISBPB to ipsilateral stellate ganglion blockade [8].…”
Section: Discussionmentioning
confidence: 99%
“…They observed that the total dose of epinephrine in the ISB was greater in patients experiencing BH while the patients who received systemic β-antagonist treatment were protected from these episodes. It has been postulated that endogenous as well as exogenous epinephrine, inducing a β-2 adrenergic effect, play a role similar to tilt-table testing in patients with unexplained syncope [9,16]. Further studies supported these hypotheses.…”
Section: Discussionmentioning
confidence: 90%
“…More recently, in 63 patients studied retrospectively with a 20.6% incidence of BH, the right operation side clearly favored the appearance of BH (R/L = 12/1 for the BH group vs R/L = 32/18 for the non-BH group) [7]. Recently, this relationship between BH and block side, with a contributing "intermediate" role of the ipsilateral stellate ganglion, is noted in a review addressing hypotensive and bradycardic events during ISB [9] and in an abstract of a prospective study implicating HRV analysis in ISB, where a significant percentage of patients showed Horner's syndrome signs [17]. Both, the review and the abstract were published after our decision to proceed with this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that injuries, both serious and minor, of other parts of the body than the head may provoke TLOC of reflex origin. Blood drawing, injection, piercing, and orthopedic arthroscopy have been reported to induce vasovagal syncope [4][5][6]. A tilt testing protocol involving subcutaneous insertion of a needle into the dorsum of hand after 10 min of passive tilt has been shown to have similar to conventional tilt protocols sensitivity and specificity [7].…”
Section: Introductionmentioning
confidence: 99%